Explication of Mosque Construction Funds from Roadside Charity Donations in the Perspective of Islamic Law Sociology - Moh. Fajrul Falah; Abu Yazid Adnan Quthny; Ahmad Muzakki (Universitas Negeri Jakarta, 2023)
This study aimed to determine the characteristics of religiosity, sociology, psychology in the controversy over mosque construction funds from roadside donations made by the people of Pakuniran District. Madura Indonesia The research method uses qualitative and ethnographic approaches, structural-functional theory, and Islamic law (IL). Ethnography is a concept of actualizing cultural aspects. Meanwhile, Talcott Parson's structural-functional theory from a socio-anthropological perspective aims to interpret society, religion and government in a linked structure. The perspective of Islamic law (IL) is a series of shari'ah of Allah Subhanahu Wa-ta'ala which is the fundamental reference for Muslims and mujtahidin in giving fatwas. So that ethnography, structural-functional, and Islamic law (IL) form a triangular methodology, which becomes a data collection and analysis technique. Results The researcher describes the perspective of roadside donation activities by formulating three fundamental data: (a) Ethnographic perspective related to roadside donation activities. (b) Structural-functional community according to the context of Talcott Parson. (c) The conformity of Islamic law (IL) to roadside charities. This study identifies the phenomenon of the Pakuniran community according to context, thereby triangulating the contradictory results between community activities and the perspective of Islamic Law (IL).